Digital platforms and the reconfiguration of politics: the formation of new political actors in the United States - Junod, Kaitlin (AUC Knowledge Fountain, 2020)
Existing approaches to studying digital platforms and politics in the context of the American landscape have focused on how “fringe” actors on the far-right and left sides of the spectrum have used social media to gain wider publicity for their ideas and values (Daniels 2018; Barnes 2020); the economic imperatives underlying the construction of platforms (Terranova 2004; Couldry and Mejias 2019); or the need for digital platforms to be regulated by lawmakers in order to protect American democracy (Hawley and Cruz 2019). However, this thesis will argue that each of these perspectives is only giving a glimpse of the overall picture. Digital platforms such as Twitter and Facebook cannot be viewed as passive tools for human actors to make use of, nor are they neutral infrastructure through which social relations are channeled. While platforms are owned and operated by private corporations for profit, the relations they give rise to exceed the relationship of user data exploitation and extraction. Furthermore, a closer examination will show both platform users and platform owners do not make sense of this relationship in solely economic terms either, but in terms of political governance. Finally, debates about how best to regulate social media miss the question of what exactly is to be regulated. This thesis will argue, using key tenets of actor-network theory as put forth by Bruno Latour, that digital platforms fundamentally reconfigure the materiality of politics, giving rise to new techno-economic formations that human actors must struggle to make sense of.